The dialogue between library and community: A case study about the profile and perceptions of the users of the community libraries of itaitinga, ceará - da Silva, Ana Pricila Celedonio; Cavalcante, Lidia Eugenia [UNESP]; Costa, Maria de Fátima Oliveira (FapUNIFESP (SciELO), 2018)
It presents a case study about the community libraries of the municipality of Itaitinga-CE. It addresses issues related to the studies of information users and their realization in local contexts. Its objectives are: to identify the profile of the users of these community libraries in Itaitinga-CE, and to investigate their perceptions about the libraries of their communities. The methodological design of the research was based on the assumptions of the case study, which analyzed three cases of community libraries located in rural areas of said municipality. The research has a mixed nature, since it includes quantitative and qualitative aspects in the data analysis, which were collected through a questionnaire. The results of the research indicate that the users of the community libraries analyzed are mostly children and young people, and a relevant participation of users of other age groups is also observed. Participants in the study reveal that they are mainly engaged in reading and cultural activities promoted by libraries. The perception of users about these spaces reveals the understanding that libraries are important for the community, especially for the possibility of access to books and reading, and cultural activities.
O diálogo entre biblioteca e comunidade: Um estudo de caso acerca do perfil e das percepções dos usuários das Bibliotecas Comunitárias de Itaitinga, Ceará
Keywords: Community Library; Library and Community; Studies of Information Users; Users in Local Contexts